Occurrence of bicuculline-, NMDA- and kainic acid-induced seizures in prenatally methamphetamine-exposed adult male rats - Slamberová, Romana; Rokyta, R (Naunyn-Schmiedeberg's archives of pharmacology, 2005)
Stimulant drugs are often associated with increased seizure susceptibility. Inhibitory gamma-aminobutyric acid (GABA) and excitatory N-methyl-D-aspartate (NMDA) systems play an important role in the effect of stimulants on epileptic seizures. No studies investigating the effect of prenatal methamphetamine (MA) exposure on seizures are available. In this study, bicuculline (GABAA receptor antagonist), NMDA (NMDA receptor agonist) and kainic acid (non-NMDA receptor agonist) were used to induce seizures in adult male rats. Three groups of animals were tested in each seizure test: prenatally MA- (5 mg/kg) exposed, prenatally saline-exposed, and absolute controls without any prenatal exposure. In bicuculline-induced seizures, the latency to onset of tonic-clonic seizures was shorter in MA-exposed rats than in controls, but it did not differ from saline-exposed rats. There were no differences in clonic seizure onset between groups. In NMDA-induced seizures, the latency to onset of clonic-tonic seizures was shorter in prenatally MA-exposed rats than in controls; however, the latency to onset of saline-exposed animals did not differ from either MA-exposed or from control rats. There were no differences in seizure susceptibility in kainic acid-induced clonic seizures. There were no differences in seizure incidences or stereotypical behavior in any seizure model. The question remains as to how much the present data demonstrate the effect of prenatal drug exposure on seizure susceptibility per se, and how much they may be explained by the effect of prenatal stress or by other mechanism(s).
Keywords: Seizures; Pregnancy; zpožděný efekt prenatální expozice; Kainic Acid; Bicuculline; agonisté excitačních aminokyselin; Female; záchvaty; krysa rodu Rattus; zvířata; stimulanty centrálního nervového systému; potkani Wistar; methamfetamin; N-Methylaspartate; GABA antagonisté; ženské pohlaví; Excitatory Amino Acid Agonists; Rats, Wistar; Male; GABA Antagonists; těhotenství; N-methylaspartát; Rats; kyselina kainová; Animals; Prenatal Exposure Delayed Effects; Central Nervous System Stimulants; mužské pohlaví; bikukulin; Methamphetamine